Colloidal nanocrystals embedded in macrocrystals : methods and applications - Adam, Marcus (2020)
Colloidal semiconductor nanocrystals have gained substantial interest as spectrally tunable and bright fluorophores for color conversion and enrichment solids. However, they suffer from limitations in processing their solutions as well as efficiency degradation in solid films. As a remedy, embedding them into crystalline host matrixes has stepped forward for superior photostability, thermal stability, and chemical durability while simultaneously sustaining high quantum yields. Here, we review three basic methods for loading the macrocrystals with nanocrystals, namely relatively slow direct embedding, as well as accelerated methods of vacuum-assisted and liquid-liquid diffusion-assisted crystallization. We discuss photophysical properties of the resulting composites and present their application in light-emitting diodes as well as their utilization for plasmonics and excitonics. Finally, we present a future outlook for the science and technology of these materials.